How an export boom affects unemployment - Noel Gaston; Gulasekaran Rajaguru (Osaka University, Institute of Social and Economic Research (ISER), 2011)
Does trade affect the equilibrium rate of unemployment? To theoretically examine this question, we incorporate firm-union bargaining considerations into a model with a booming external sector and a stagnating manufacturing sector. In the model, a sustained improvement in the terms of trade lowers unemployment. To empirically investigate the predicted determinants of the unemployment rate, we use data for Australia, a country whose prosperity has always depended on the value of its exports. We find strong evidence that higher export prices, capital accumulation in tradeable goods industries and a lower unemployment benefit replacement rate each reduce the equilibrium unemployment rate.
Keywords: E24; F12; J51; 330; equilibrium unemployment rate; specific factors model; bargaining; mining boom; Dutch disease; Arbeitsmarkttheorie; Terms of Trade; Beschäftigungseffekt; Bergbauerzeugnis; Außenhandel; Rohstoffreichtum; Australien